Salvia officinalis L. exerts oncostatic effects in rodent and in vitro models of breast carcinoma - Kubatka, Peter; Mazurakova, Alena; Koklesova, Lenka; Kuruc, Tomas; Samec, Marek; Kajo, Karol; Kotorova, Klaudia; Adamkov, Marian; Smejkal, Karel; Svajdlenka, Emil; Dvorska, Dana; Brany, Dusan; et al. (Frontiers in Pharmacology, 2024)
Based on extensive data from oncology research, targeting specific molecular pathways with phytochemicals is considered an innovative approach to cancer management. This research aimed to analyze the oncostatic properties of Salvia officinalis L. [Lamiaceae; Salviae officinalis herba] using animal and in vitro models of breast carcinoma (BC). The effects of dietary administered S. officinalis in two concentrations (0.1 % /SAL 0.1/ and 1 % /SAL 1/) were assessed in both syngeneic 4T1 mouse and chemically induced rat models of BC. The histopathological and molecular evaluations of rodent carcinoma specimens were performed after the autopsy. Besides, numerous in vitro analyses using two human cancer cell lines were performed. The dominant metabolites found in S. officinalis propylene glycol extract (SPGE) were representatives of phenolics, specifically rosmarinic, protocatechuic, and salicylic acids. Furthermore, the occurrence of triterpenoids ursolic and oleanolic acid was proved in SPGE. In a mouse model, a non-significant tumor volume decrease after S. officinalis treatment was associated with a significant reduction in the mitotic activity index of 4T1 tumors by 37.5 % (SAL 0.1) and 31.5 % (SAL 1) vs. controls (set as a blank group with not applied salvia in the diet). In addition, salvia at higher doses significantly decreased necrosis/whole tumor area ratio by 46 % when compared to control tumor samples. In a rat chemoprevention study, S. officinalis at a higher dose significantly lengthened the latency of tumors by 8.5 days and significantly improved the high/low-grade carcinomas ratio vs. controls in both doses. Analyses of the mechanisms of anticancer activities of S. officinalis included well-validated prognostic, predictive, and diagnostic biomarkers that are applied in both oncology practice and preclinical investigation. Our assessment in vivo revealed numerous significant changes after a comparison of treated vs. untreated cancer cells. In this regard, we found an overexpression in caspase-3, an increased Bax/Bcl-2 ratio, and a decrease in MDA, ALDH1, and EpCam expression. In addition, salvia reduced TGF- serum levels in rats (decrease in IL-6 and TNF-levels were with borderline significance). Evaluation of epigenetic modifications in rat cancer specimens in vivo revealed a decline in the lysine methylations of H3K4m3 and an